2016
DOI: 10.1210/me.2015-1277
|View full text |Cite
|
Sign up to set email alerts
|

HRD1-Mediated IGF-1R Ubiquitination Contributes to Renal Protection of Resveratrol in db/db Mice

Abstract: Many studies have provided evidence to demonstrate the beneficial renal effects of resveratrol (RESV) due to its antioxidant character and its capacity for activation of surtuin 1. However, the molecular mechanisms underlying the protective role of RESV against kidney injury are still incompletely understood. The present study used Lepr db/db (db/db) and Lepr db/m (db/m) mice as models to evaluate the effect of RESV on diabetic nephropathy (DN). RESV reduced proteinuria and attenuated the progress of renal fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
(44 reference statements)
1
25
0
Order By: Relevance
“…2b ) and quantification of HRD1 expression (Fig. 2c ), which is consistent with our previous work 19 . Meanwhile, in the present study, the decreased HRD1 protein in db/db mice was also verified by immunohistochemical staining of kidney tissues of db/db mice as shown in Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…2b ) and quantification of HRD1 expression (Fig. 2c ), which is consistent with our previous work 19 . Meanwhile, in the present study, the decreased HRD1 protein in db/db mice was also verified by immunohistochemical staining of kidney tissues of db/db mice as shown in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Activation of the PERK-eIF2α-ATF4 pathway confirms that eIF2α plays an important role in ER stress-induced apoptosis. Our previous LC-MS/MS analysis of injured tubular epithelial cells (HKC-8) revealed that eIF2α was a substrate of 3-hydroxy-3-methylglutaryl reductase degradation protein (HRD1), an ERAD-associated E3 ubiquitin ligase 19 . HRD1 physically promotes the degradation of proteins in processes such as renal injury and obesity 19 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol, a phytoestrogen, is a naturally occurring phenol compound which is structurally and functionally similar to estrogen [ 31 ]. Recently, data showed that orally administering resveratrol (40 mg/kg/day, a high dose) decreased albuminuria and attenuated the progression of kidney fibrosis in db/db mice [ 32 , 33 ]. In contrast, a paper described that oral resveratrol at 0.5 mg/kg (a low dose) ameliorated DM symptoms and improved insulin resistance in a STZ-induced DM model [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein digestion, labeling, mass spectrometry data acquisition, and identification were completed in the analysis center of Nanjing Medical University. Briefly, a LTQ-Orbitrap instrument (Thermo Fisher, USA) connected to a Nano ACQUITY UPLC system was used to analyze the labeled the peptide samples, as described previously, as well as the acquired MS/ MS spectra and parameters 19,20 .…”
Section: Mass Spectrometrymentioning
confidence: 99%